Enhanced resistance to decay of imprinted nanopatterns in thin films by bare nanoparticles compared to polymer-grafted nanoparticles. Issue 18 (16th August 2021) - Bhadauriya, Sonal; Nallapaneni, Asritha; Wang, Xiaoteng; Zhang, Jianan; Masud, Ali; Bockstaller, Michael R.; Al-Enizi, Abdullah M.; Stafford, Christopher M.; Douglas, Jack F.; Karim, Alamgir
Abstract : Resistance to height decay of imprinted nanocomposite patterns: bare NPs > grafted NPs > neat PMMA. Abstract : We extend a previous study on the influence of nanoparticles on the decay of nanoimprinted polymer film patterns to compare the effects of "bare" silica (SiO2 ) nanoparticles and SiO2 nanoparticles with grafted polymer layers having the same chemical composition as the polymer matrix. This method involves nanoimprinting substrate-supported polymer films using a pattern replicated from a digital versatile disc (DVD), and then annealing the patterned polymer nanocomposite films at elevated temperatures to follow the decay of the topographic surface pattern with time by atomic force microscopy imaging after quenching. We quantified the relaxation of the pattern height ("slumping") and determined the relaxation time τ for this pattern decay process as a function of nanoparticle filler type and concentration to determine how nanoparticle additives influence relative film stability. Attractive interactions between the bare nanoparticles and the polymer matrix significantly enhance the thermal resilience of the nanopatterns to decay, compared to those of the particle brushes, wherein the particle core interactions are screened from the matrix via the brush layer. A novel aspect of this method is that it readily lends itself to in situ film relaxation measurements in a manufacturing context. We observe that the relaxation time of the pattern relaxation exhibits entropy–enthalpy compensation in the free energy parameters governing the pattern relaxation process as a function of temperature, irrespective of the NP system used, consistent with our previous experimental and computational studies.